The potential Geographic Information System (GIS) in water distribution system in UiTM Shah Alam / Nurul Hashimah Adnan - Adnan, Nurul Hashimah (Faculty Architecture, Planninng and Surveying, 2014)
GIS is a summary of the Geographic Information System considers GIS as a system involving hardware of software, data, user, organization and effective management to collect, store analyse and present information related to various area of the world. In GIS initially developed to help cartographers but now it has become a tool of modelling and key management in the field of engineering such as water supply management. GIS capable of combining attribute data and spatial data in system and performed various analyse related with a network of water distribution system. GIS system can speed manual search for information, updates and analysis of the data. GIS capabilities compared with other CAD system and it selected to develop a water utility management. Therefore, this research conducted with the purpose the design base on GIS water distribution system at UiTM Shah Alam. Therefore, this research to study the types of layout of water distribution system, second analysis is to identify the possible application of GIS in water distribution system and third analysis to establish a water distribution system based on GIS application The end of this research will provide suggestions to provide the database will ease the monitor and maintenance of water supply distribution pipeline system for UiTM Shah Alam Facilities Department using GIS system. GIS system implement at facilities department because it ease the water management and it can speed search for information updates and getting the data. GIS system can create a database for inventory. GIS also use to helps improve management information system and databases.